Administration of polysaccharide K (PSK) for stage III rectal cancer in clinical practice - Ishibashi, Keiichiro; Hokama, Naoko; Ishiguro, Toru; Kuwabara, Kouki; Okada, Norimichi; Ohsawa, Tomonori; Miyazaki, Tatsuya; Yokoyama, Masaru; Ishida, Hideyuki (Gan to kagaku ryoho, 2009)
This retrospective study was performed to examine the frequency of PSK administration in patients with Stage III rectal cancer in clinical practice, and the effect of PSK on patient outcome. The subjects were 71 patients with Stage III rectal cancer who received postoperative adjuvant chemotherapy comprising fluoropyrimidines between April 1997 and March 2006. The frequency of PSK administration and factors affecting recurrence, disease-free survival, and overall survival were examined. The frequency of concomitant use of PSK with fluoropyrimidines was 79% (56 patients). Among the patients who were given PSK, the frequency of concomitant use of UFT alone was higher in Stage III a patients, while the rate of concomitant use of fluoropyrimidines and Leucovorin was higher in Stage III b patients (p<0.01). Multivariate analyses revealed that the only predictive factor affecting recurrence, disease-free survival, and overall survival was Stage III b. Although the rate of concomitant use of PSK in adjuvant chemotherapy for patients with Stage III rectal cancer was high, we did not evaluate the effect of PSK because there was a marked bias in relation to the subclassification of Stage III disease and the use of Leucovorin in these subjects. Prospective randomized trials with stratification of Stage III disease will be needed in the future to validate the efficacy of PSK.